Droga inicjacji chrześcijańskiej w Kościele starożytnym na podstawie katechez Cyryla Jerozolimskiego - Jędrzejewska, Małgorzata (Vox Patrum, 2003)
Cyril is one of the most prominent persons of young Christian Church and also most important witnesses of Christian initiation in this Church. He’s an author of Catechesis - one of most valuable treasures and most current writings of Christian antiquity as far as message is concerned. The Catechesis clearly introduce the way of Christian initiation, the way of initiation into subsequent truths of beliefs, which I will attempt to discover and present. They also deliver necessary (independent from time and places) sensibility of spirit and Christian rules. In present article I will try to answer the questions: whether nowadays this first, initial forms of initiation, about which we inquire from described here Catechesis, are able to influence as considerably, as they did 2000 years ago? Can they similarly affect the manners of modern children and youth?